442 RCPCH trainee charter audit: perceptions of trainers vs. trainees. (17th August 2022) - Francis, Sunil
Abstract : Aims: The RCPCH Trainee Charter sets expectations for trainees of their training centres and provides a standard for high quality local training. Adherence to the principles is requested from the CQC when Trusts are inspected, and responses are provided by the College Tutor. However, no work has been done to assess the perceptions of trainees, and how these might differ from trainers. My aim was a pilot to address whether there is a difference in perception amongst the different domains of the trainee charter, and if there are differences what is the magnitude and possible reasons for this. Methods: Paediatric trainees (ST1-7) at the Derbyshire Children's Hospital and consultant trainers were approached to complete a perception survey over a 2-week period. Each statement within the Trainee Charter was stated, and participants asked to rate their perception of the training unit's performance with respect to that statement on a 4-point Likert scale. A free text box was included for any further information participants wanted to confer. The form was hosted on Google Forms and the survey reviewed by the author of this work (paediatric registrar, and did not contribute to the survey). Results: Responses were gathered from 8 trainees and 13 trainers. Mean scores reported in figure 1 and a visual representation of the difference is represented in figure 2. Conclusion: The trainee charter exists to provide a quality standard for training centres. Whilst it is not possible for training centres to be perfect, audit of a training centre's perceived adherence to the standard is important to ensure quality is maintained. In this study we have found discrepancy, and because of this an intended quality improvement project to improve the quality in our local training centre has been proposed. This will continually review the charter within our centre and highlight issues to promote change ideas to accountably improve training quality.